Dampak Waktu Kerja Fleksibel Dalam Meningkatkan Employee Engagement. Studi pada Perusahaan Layanan Jasa Konstruksi di Indonesia - Elfie Johanes; MC. Oetami P (Jurnal Manajemen dan Bisnis Indonesia, 2016)
The study intend to analyze the impact of the Flexible Working Time and Performance to improve Employee Engagement in company in Indonesia. The subjects were 45 employees of Construction Consulting Firm in Jakarta. Type of research is quantitative with multiple regression analysis method to explain that there is a significant influence in the implementation of Flexible Working Time to improve Employee Engagement. Employee Performance also showed a considerable impact on Employee Engagement, and jointly Flexible Working Time and Employee Performance create an essential effect to Employee Engagement. This study suggested that Flexible Working Time can be considered to be applied in such type of construction consulting firm in Jakarta to increase Employee Engagement.